Extraction and identification of vitamin E from Pithecellobium Jiringan seeds using supercritical carbon dioxide - Che Yunus, Mohd. Azizi (Penerbit UTM Press, 2015)
Pithecellobium Jiringan (P. Jiringan) is traditionally known as natural herb consists of several medicinal compounds (vitamin E). Supercritical carbon dioxide extraction (SC-CO2) has been proven as potential method to extract interest compound from herbs. By altering pressure and temperature, the specific compound can be extracted. In this study, the SC-CO2 operating conditions are pressure (20.68 MPa to 55.16 MPa) and temperature (40°C to 80°C) in one hour extraction regime was used to extract vitamin E from P. jiringan. The quantification of vitamin E was analysed with Gas Chromatography Time of Flight Mass Spectrometry (GC-TOF-MS). The responses are overall oil yield and vitamin E yield. The overall oil yield was obtained at the highest condition of 55.16 MPa and 80°C with asymptotic yield of 8.06%. In contrast, the highest amount of vitamin E obtained is 0.0458mg/g sample (80.14 ppm) at the lowest extraction condition of 20.68 MPa and 40ᵒC